2017
DOI: 10.5812/pedinfect.61605
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytosis in Under-Five Children with Lower Respiratory Tract Infection

Abstract: Background and Objectives: Thrombocytosis is a marker of inflammatory reaction with various clinical outcomes. The current study aimed at evaluating the incidence and significance of degree of thrombocytosis in relation to severity of the pneumonia in children less than 5 years old with lower respiratory tract infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
(17 reference statements)
1
4
0
Order By: Relevance
“…MPV and PDW are two key platelet markers associated with inflammation. MPV and PDW levels in pneumonia patients were lower than in the control group in our study, as previously reported (2,(27)(28)(29)(30). The level of MPV was reported to decrease with the severity of the pneumonia however we did not find an association between MPV and CAP severity.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…MPV and PDW are two key platelet markers associated with inflammation. MPV and PDW levels in pneumonia patients were lower than in the control group in our study, as previously reported (2,(27)(28)(29)(30). The level of MPV was reported to decrease with the severity of the pneumonia however we did not find an association between MPV and CAP severity.…”
Section: Discussionsupporting
confidence: 70%
“…Platelets are essential inflammation cells that generate a big portion of cytokines and also can behave as acute phase reactants as well. Platelet counts were reported to be higher in children with pneumonia (27,28).…”
Section: Discussionmentioning
confidence: 97%
“…For example during respiratory tract infection, there are increasing levels of inflammatory cytokines which heightens the production of thrombocytes. 33 In contrast, thrombocytopenia was observed by 8% (95% CI: 4.59–11.34). The decrement of platelet count in the current study was in agreement with previous studies.…”
Section: Discussionmentioning
confidence: 96%
“… 32 Thrombocytosis is another hematological alteration in undernourished children that could be associated with infection. 33 In Ethiopia, undernutrition is a major public health problem and a preliminary diagnosis in 20% of pediatric hospital admissions. 34 The fatal effect of the disease in relation to hematological features is one concern where attentions have not yet got.…”
Section: Introductionmentioning
confidence: 99%
“…6 Platelet count elevated more than normal is often sign of severe pneumonia according to various studies. 7…”
Section: Introductionmentioning
confidence: 99%